INFITA-THERAPY ROLE IN THE REHABILITATION OF PATIENTS WITH OCCUPATIONAL DISEASES - Филимонов, Сергей Николаевич; Матвеева, Оксана Владимировна; Москалева, Татьяна Сергеевна; Герасимова, Галина Анатольевна (Medicine in Kuzbass, 2023)
It has been established that the use of pulsed low-frequency electromagnetic fields of non-thermal intensity, which have a stimulating effect on the central nervous system, improve the bioelectrical activity of the brain and the psychological state of the patient. Objective of research – to evaluate the effectiveness of the physiotherapeutic method of treatment – infitatherapy in patients with occupational diseases – vibration disease and chronic obstructive pulmonary disease. Material and methods. In the patients with occupational pathology, before and after physiotherapy using the INFITA-M device, an evaluation of the disorders in the psycho-emotional sphere according to the eight-color Lüscher test and an assessment of the adaptation response by the method of L.Kh. Garkavi with the determination of the ratio of the number of cells in the leukocyte blood formula. For mathematical processing of the material, indices of non-parametric statistics and the program «Statistica 6.0» with a value of P < 0.05 were used. Results. The influence of infita-therapy on the patients with occupational pulmonary diseases and vibration disease at the stage of sanatorium-resort rehabilitation was studied. It was shown that infita-therapy helped to reduce the level of anxiety, restore the physiological level of adaptation, increase the importance of positive attitudes to life situations. Limitations. 25 patients with occupational pathology who got infita-therapy and 25 people in the control group were examined. In the future, it is desirable to increase the number of patients in the group with occupational diseases. Conclusion. Treatment on the INFITA-M device (basic module) leads to the normalization of the functions of the autonomic and central nervous systems, reduces the levels of stress and anxiety in the patients with occupational diseases at the stage of rehabilitation, which increases the effectiveness of rehabilitation programs.